Unlocking the potential of collagen: A comprehensive review on its dermocosmetic benefits and applications - Felicia Andrei; Ana Toma; Ștefania Avram; Valentin Popa; Ioana Gencia; Patricia Cristodor (Brazilian Journal of Pharmaceutical Sciences)
Abstract Collagen, the predominant protein in various organisms, is pivotal for tissue structure and mechanical properties. It has been extensively studied for its cosmetic, surgical, and anti-ageing applications, reflecting a growing interest in collagen-based cosmetics in Romania and prompting further research in this area. The study aimed to assess collagen’s efficacy and safety in dermocosmetology, comparing collagen peptides’ effectiveness in oral and topical applications. An analysis of the published studies on the subject was carried out, comparing the effectiveness of using collagen in different ways to improve skin conditions. The investigation included a literature review on collagen’s role in enhancing skin properties, covering its discovery, structure, chemical composition, systemic and topical applications, diverse sources, and skin penetration mechanisms. Hydrolysed collagen and its antioxidant properties are considered. The methods of investigating and monitoring the safety of cosmetic preparations are described. It has been concluded that topical collagen, similarly to nutraceutical supplements with collagen peptides, can slow down and reduce the signs of skin ageing and can increase skin elasticity, density, and moisture in equal measure. Studies have confirmed the harmlessness of collagen beyond doubt, but further investigation is necessary to determine the effectiveness of using different types of collagen.